Bridging AI-TPACK and STEM education: Navigating facilitators, barriers, and ethical dimensions through a systematic review - Ataran, Atefeh; shojaei, Ladan (American Journal of STEM Education, 2026)
Artificial intelligence (AI) can play a transformative role in STEM education, although its integration presents pedagogical, technological, and ethical challenges. This review synthesizes interdisciplinary perspectives on AI integration in K–12 STEM classrooms through the AI Technological Pedagogical Content Knowledge (AI-TPACK) framework. Using PRISMA guidelines, 38 empirical studies published between 2018 and 2025 were analyzed through deductive coding. Findings indicate that AI can support the visualization of STEM content, enable adaptive feedback, and foster collaborative learning environments. However, these opportunities are constrained by infrastructure limitations, insufficient teacher preparation, and misalignment between AI tools and curriculum goals. Ethical concerns related to privacy, bias, and transparency emerged as central challenges. This study offers recommendations for the sustainable integration of AI in STEM education.